Design and Implementation of a 4x2 Diamond Patch Array Microstrip Antenna with I-Slot for 2.4 GHz Frequency - Arya, Ade Dwi; Koesmarijanto, Koesmarijanto; Hudiono, Hudiono (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
As communication technology continues to evolve rapidly, particularly in the field of wireless communication, there is a growing demand for high-speed, efficient, and high-quality communication systems due to the increasing mobility of society. Microstrip antennas offer the advantages of being small, inexpensive, and lightweight. However, these antennas typically have low gain and bandwidth. Various methods have been proposed to enhance the gain of microstrip antennas, such as the addition of slots to the patch. This research presents an external device, a microstrip antenna, that can increase data transfer capacity and operates at the Wi-Fi frequency of 2.4 GHz. The fabricated 4x2 I-Slot Diamond Patch Array Microstrip Antenna demonstrates improved performance with a measured return loss of -17.3 dB and VSWR of 1.3 at 2.4 GHz. The incorporation of the I-slot and array configuration results in a bandwidth of 105 MHz, which is 9 MHz wider compared to a similar antenna without the slot (96 MHz). In outdoor range testing, the proposed antenna achieves a maximum communication distance of 30 meters with an RSSI of -72 dBm, outperforming the built-in antenna which yields -77 dBm at the same distance.